Desafios metodológicos em epidemiologia: uma abordagem com foco na reação adversa da trombocitopenia induzida por heparina e na condição clínica da dor lombar - Daniela Rezende Garcia Junqueira (2012)
The focus on the biomedical model which is a central aspect of the health interventions of the contemporary times omits nuances of the therapeutic process with medicines, and of failures of that process. Therefore, the appropriate managing of the use of medicines requires a paradigm shift regarding the guarantee of effective pharmacological interventions but also safe ones, in addition to alternative strategies in the absence of these fundamental pillars. Some of the challenges to this paradigm shift are exemplified by two public health problems: the adverse drug reactions and the complex health problems. In both contexts, the pharmacologic interventions sometimes do not provide the necessary safety and sometimes not exert a therapeutic effect according to the presumed effectiveness. This thesis follows the path for the design and application of unique epidemiological methods approaching these problems and challenges focusing on an adverse drug reaction (the heparin-induced thrombocytopenia) and on a complex health problem (the low back pain). Taking this perspective in account, this scientific work structures two research lines named: Epidemiology of adverse drug reactions and Genetic epidemiology and twin study. The results are organized in five original articles, presented in the form of publication or submission. Considering the research line Epidemiology of adverse reactions we should highlight as main results: our studies showed the heterogeneity of the heparins commercialised in Brazil, a situation with potential impact in the safety profile of the drug and in the risk of heparin-induced thrombocytopenia; we were able to ascertain the lower risk of heparin-induced thrombocytopenia in patients exposed to low molecular weight heparin when compared to patients exposed to unfractionated heparin; it was demonstrated a paucity of randomized controlled trials addressing the safety aspect of the use of heparins; and we were able to generate health information for professionals and for the national and international pharmacovigilance system about safety aspects related to the use of heparins in Brazil and about the heparin-induced thrombocytopenia. Considering the research line Genetic epidemiology and twin study we should highlight as main results: we were able to study the influence of the genetic component in chronic low back pain showing its major contribution in the prevalence of this chronic condition; and our studies showed an important contribution of domestic physical workload but not leisure physical activity to chronic low back pain. These results contribute to a comprehensive understanding of the process of drug utilization and represent a positive contribution for the knowledge generation regarding the safe use of medicines and the risk assessment of complex diseases. We also believe that the knowledge behind these results may support the design of new clinical protocols and public health strategies considering the use of heparin and the low back pain problem. We also emphasize that both research lines are incipient in Brazil and, from this perspective, this thesis embodies the expectations of scientific innovation and of international partnerships as a strategy to the development of national researches with competitive calibre which may encourage the scientific advancement of the country.